The potential effect of age on the natural behavior of bladder cancer: Does urothelial cell carcinoma progress differently in various age groups?. Issue 5 (10th April 2016) - Gunlusoy, Bulent; Ceylan, Yasin; Degirmenci, Tansu; Aydogdu, Ozgu; Bozkurt, Ibrahim Halil; Yonguc, Tarik; Sen, Volkan; Kozacioglu, Zafer
Abstract: We aimed to evaluate the potential effect of age on the natural behavior of bladder cancer and to compare these findings between different age groups. The clinical and pathologic data of 239 patients treated at our institution between 1994 and 2014 were analyzed. The patients were classified into three groups according to age: ≤ 40 years (Group 1), 41–59 years (Group 2), and ≥ 60 years (Group 3). The following data were collected: characteristics of the patients, initial pathological findings after transurethral resection, tumor stage and grade, tumor size and multiplicity, and disease recurrence and progression. The mean age of the patients at initial diagnosis was 34.2 ± 5.5 years, 53 ± 5.1 years, and 71.1 ± 7 years in Groups 1, 2, and 3, respectively. There were 207 (86.6%) patients with nonmuscle‐invasive urothelial bladder cancer and 32 (13.4%) patients with muscle‐invasive disease. Tumor recurrence was significantly lower in Group 1 than in Group 2 ( p = 0.001) and Group 3 ( p = 0.001). Although the time to tumor recurrence was significantly different between the three groups ( p = 0.001), no significant difference was noted in the time to progression ( p = 0.349). Patients with urothelial cancer younger than 40 years tend to have single and small tumors. The tumor recurrence rate is lower in the younger age group, but tumor progression is similar in older and younger patients. Therefore, the findings indicate that clinicians should be careful when assessing the invasiveness of urothelial tumors in younger patients and start treatment as soon as possible.